EMPOWERING RURAL COMMUNITIES THROUGH AGRICULTURAL TRANSFORMATION: A CASE STUDY IN BONDOWOSO - Rahma, Siti Habibatur; Mondir, Mohamad (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Food security is an important issue in agriculture-based rural development in Indonesia. This study focuses on the empowerment of the community of Sukosari Kidul Village, Sumberwringin Subdistrict, Bondowoso Regency through a food security program. The study aims to analyze how the program is implemented and what factors determine its success. This research uses a descriptive qualitative method with a literature review approach, data was obtained from journals, books, policy documents, and relevant news articles. The results indicate that the program's success is determined by the synergy between the village government, farmer groups, and community leaders. The activities carried out include the construction of farm access roads and the provision of food storage facilities, supported by funding from the state budget. empowering process was carried out in a participatory manner, from planning to evaluation, which ultimately had a positive impact on community welfare and the sustainability of the agricultural sector. This study emphasizes the importance of a collaborative approach in building food security at the village level.